What do strawberries and hoverflies have in common? Unwanted effects of anthelmintics on non target organisms - García, Andrés (Agrar- und Ernährungswissenschaftliche Fakultät der CAU, Christian-Albrechts-Universität Kiel (Alemania), 2025)
Presentación en diapositivas